Analisis Kepuasan Mahasiswa ST Ilmu Komputer Cipta Karya Informatika Pada Kualitas Layanan Akademik Dengan Metode Servqual - Rodhiyah, Rodhiyah; Veriarinal, Veriarinal (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Siliwangi, 2025)
This study aims to analyze student satisfaction with the quality of academic services at ST Ilmu Komputer Cipta Karya Informatika using the SERVQUAL approach. The method measures the gap between students’ expectations and perceptions across five service dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data were collected via questionnaires distributed to 149 students and analyzed by comparing perception and expectation scores. The results show that all service dimensions had quality ratios below 1, indicating that service delivery does not fully meet student expectations. Empathy received the highest scores of 0.93, while reliability recorded the lowest scores of 0.87. These findings highlight the need for service improvement, particularly in the areas of reliability and timely response to student needs. Recommendations include enhancing academic information systems, ensuring consistency in academic services, and improving staff professionalism.Keywords: Student Satisfaction, Service Quality, Higher Education